Aspek Hukum Perlakuan Pajak Pertambahan Nilai Terhadap Transaksi Perdagangan Elektronik Di Indonesia - Anita Sari; Syafruddin Makmur (JOURNAL of LEGAL RESEARCH, 2019)
Abstract.This study aims to measure the tax treatment of electronic transactions that have been carried out by the Government in electronic commerce transactions (e-commerce). In the transaction activities that occur in E-Commerce basically there is a potential tax that can help the country's economy, but the tax collection that took place has not been addressed properly. Other obstacles in tax collection, especially Value Added Tax (VAT), are related to the difficulty of determining the parties involved in transactions in E-Commerce and the characteristics of intangible goods traded. This research uses the Law approach with empirical normative research type. The results of this study indicate that regulations that have been issued by the Government, namely PMK Number 210 / PMK / 010/2018 About Taxation Treatment of Trade Transactions Through Electronic Systems (E-Commerce) have not been maximized in addressing electronic commerce (e-commerce) that occurs in Indonesia especially on rules that apply taxation on electronic transactions.Keywords: Value Added Tax, E-Commerce, Electronic Contracts